2006
DOI: 10.1016/j.trstmh.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii infection among pre-schoolchildren aged 1–5 years in the Democratic Republic of Sao Tome and Principe, Western Africa

Abstract: The prevalence status of Toxoplasma gondii infection in children of the Democratic Republic of Sao Tome and Principe (DRSTP), Western Africa, is unknown to date. A serologic survey of T. gondii infection among pre-schoolchildren aged <5 years in the DRSTP was assessed by the latex agglutination (LA) test from November 2003 to March 2004. The overall seroprevalence of T. gondii infection was not low, reaching 21.49% (26/121). No significant gender difference in seroprevalence was found between boys (19.30%; 11/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…Substantial studies have indicated that the seroprevalence of T. gondii infection increases with age (10) (39) , and one hypothesis suggests that this outcome is the result of an increasing number of exposure years as the child grows (40) . There was an increasing pattern of infection rates with age in this study as well, but the trend was not statistically signifi cant, which may have been due to the small sample numbers in some age groups making it diffi cult to demonstrate a difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial studies have indicated that the seroprevalence of T. gondii infection increases with age (10) (39) , and one hypothesis suggests that this outcome is the result of an increasing number of exposure years as the child grows (40) . There was an increasing pattern of infection rates with age in this study as well, but the trend was not statistically signifi cant, which may have been due to the small sample numbers in some age groups making it diffi cult to demonstrate a difference.…”
Section: Discussionmentioning
confidence: 99%
“…The way a cat's litter box is cleaned seems to account for exposure to the parasite rather than the mere presence of cats in the household; in our study, most cat owners used gloves while cleaning the litter box. The lack of an association between cat ownership and infection could also suggest that environmental contamination by cats is so widespread that cat ownership has minimal effects on the level of exposure to T. gondii (39) .…”
Section: Discussionmentioning
confidence: 99%
“…The LA test was used to screen T. gondii infection using commercial reagents (TOXO Test-MT; Eiken Co. Ltd., Tokyo, Japan). The LA test has been widely employed in several remote or isolated regions because of its high sensitivity, specificity, and ease of operation (9)(10)(11)(12)(13)(14). Positive sera samples were determined using a cutoff titer of 132.…”
Section: Methodsmentioning
confidence: 99%
“…Most clinical laboratories therefore utilize serological tests such as latex agglutination (LA) test, enzyme-linked immunosorbent assay, and indirect fluorescent antibody test to detect antibodies against T. gondii in infected individuals. The LA test has been widely used in remote areas of developing countries because of its high specificity and sensitivity as well as convenience (8)(9)(10)(11)(12)(13)(14). Serological surveys of T. gondii infection have been conducted in several regions; however, seroprevalence rates vary between investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Nous constatons toutefois des différences de préva-lence avec des zones de savanes gabonaises (Beauvais et al, 1978 ;Billiault et al, 1987) et d'autres pays de l'Afrique de l'ouest tels que le Nigéria (Uneke et al, 2007) et de l'Afrique de l'est comme l'Ethiopie (Negash et al, 2008). Dans notre échantillon, la séroprévalence chez les enfants de moins de cinq ans était proche de celles observées à Libreville (Duong et al, 1992), en milieu urbain, et sur l'île de Sao Tomé et Principe qui dispose des mêmes conditions géoclimatiques (Fan et al, 2006). Ces élé-ments plaideraient pour une transmission précoce et stable dans la sous région.…”
unclassified